2001
DOI: 10.1002/1522-2683(200105)22:8<1484::aid-elps1484>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification ofL-ascorbic acid and total ascorbic acid in fruits and spinach by capillary zone electrophoresis

Abstract: A standard curve for the quantification of L-ascorbic acid (L-AA) by capillary zone electrophoresis (CZE) was established, and the quantification of ascorbic acid and total ascorbic acid in fruits (lemon, Sunkist, and pineapple) and spinach were performed using D-isoascorbic acid (D-IAA) as an internal standard. The minimum detection limits (MDLs) for L-AA and D-IAA were determined to be 1 and 2 microg/mL, respectively, at 265 nm. Dehydroascorbic acid (DHAA) in fruits and spinach was quantified in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…First three additions are 10 ll and the fourth addition is 100 ll of lemon juice. The concentration of AA was calculated and found to be 339 lg ml -1 , which is very close to the value determined by capillary zone electrophoresis [65].…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…First three additions are 10 ll and the fourth addition is 100 ll of lemon juice. The concentration of AA was calculated and found to be 339 lg ml -1 , which is very close to the value determined by capillary zone electrophoresis [65].…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…However, this method presents the opportunity to utilize D-isoascorbic acid as an internal standard for quantification of L-ascorbic acid. Indeed, the authors reported this application recently for the quantification of L-ascorbic acid and total ascorbic acid in fruits and spinach [32].…”
Section: Vitaminsmentioning
confidence: 79%
“…Despite of that fact the kinetics of electron transfer are still quite sluggish and fast degradation of the attached or adsorbed materials results in a difficulty to be used for these purposes. Recently, the quantification of AA and total AA in food, fruits and spinach by capillary-zone electrophoresis and/or chromatography 8,9 has been reported.…”
Section: Introductionmentioning
confidence: 93%